Sclerochronological insights into the environmental response of Corbula gibba from the Adriatic Sea - Strafella, Pierluigi; al-Fudhaili, Najat; de Winter, N.; López Correa, Matthias; Teichert, Sebastian; Scarcella, G; Nohl, Theresa (EGU General Assembly 2022, 2022)
Bivalve shells are accretionary biogenic carbonates that yield a record of the organisms’ life history, also with respect to the physiological response to the ambient environmental conditions. This is reflected by variations in the shells’ growth bands, their chemical composition, and morphological features, making them useful tools in paleobiology and paleoenvironmental reconstructions. Corbula gibba is an abundant bivalve species in the Adriatic Sea that is commonly used to resolve questions in age determinations, paleoenvironmental reconstructions and sequence stratigraphic studies [1,2]. Nevertheless, a detailed analysis of its response in growth bands and chemical signatures to environmental variations is currently missing. This study evaluates growth increments and chemical variations in Corbula gibba shells. The shells have been collected alive from the Western Adriatic Sea between Senigallia and Ancona to shed light on the reliability of the Corbula gibba as an archive for (paleo)environmental information. Mutvei's solution has been used [3] to stain the alternating dark and light bundles in the shell, enhancing the visualization of growth increments. High-resolution elemental profiles have been acquired across the outer shells layer using the non-destructive Micro X-ray fluorescence (µ-XRF) technique [4]. The results are compared to available climatic information for Ancona and indicate that Corbula gibba shells record detailed temporal changes in the environment such as tidal fluctuations caused by lunar cycl